Activity of A-56268 compared with that of erythromycin and other oral agents against aerobic and anaerobic bacteria. - Chin, N X (1987)
A-56268 was compared with erythromycin, roxithromycin (RU 28965), and perorally administered antimicrobial agents. Its in vitro activity was similar to that of erythromycin and slightly greater than that of roxithromycin, with beta-hemolytic streptococci and Streptococcus pneumoniae inhibited by less than 2 micrograms of A-56268 per ml (50% inhibited by 0.06 microgram/ml). Streptococcus pyogenes, S. agalactiae, S. Pneumoniae, and S. faecalis resistant to erythromycin were resistant to A-56268, and 4 micrograms/ml inhibited 90% of Haemophilus influenzae isolates.